Wybrane źródła konfliktów pomiędzy poszkodowanymi a zakładami ubezpieczeń w procesie likwidacji szkód komunikacyjnych - Kiełbasa, Monika (Chosen Sources of Conflicts Between Injured Parties and Insurance Companies in a Process of Liquidation of Communicational Damages, 2006)
Differences between repair costs of damaged vehicle confirmed by invoice and amount of the claim calculated by the insurer, are frequently causing conflicts among participants of claims handling process. These differences are lawful thanks to general conditions of insurance and limitations of the scope of insurer's obligations. There are rules presented concerning the calculating of insurance premium in the motor insurance.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (5); 2006; nr 1120, s. 94-108